THE PRINCIPAL COMPONENT ANALYSIS AS RURAL DEVELOPMENT LEVEL ASSESSING METHOD IN THE REPUBLIC OF MOLDOVA IN THE CONTEXT OF REDUCING SOCIAL EXCLUSION - Alexandru GORGOS; Iurie DANILOV; Nina PUȚUNTEAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper is to define the principal component analysis method for assessing the rural development level in the Republic of Moldova. The results of mathematical processing of primary data obtained as a result of surveying 9 rural localities using the Date Envelopment Analysis are presented. Applying the rating method as a key indicator of sustainable development it provides a comprehensive approach to the rural area issues. Socio-economic and ecological characteristics of the evaluated sample are also evaluated.